Conditioned Fear Associated Phenotypes as Robust, Translational Indices of Trauma-, Stressor-, and Anxiety-Related Behaviors - Briscione, Maria Anne; Jovanovic, Tanja; Norrholm, Seth Davin (Frontiers in Psychiatry, 2014)
Posttraumatic stress disorder (PTSD) is a heterogeneous disorder that affects individuals exposed to trauma (e.g., combat, interpersonal violence, and natural disasters). It is characterized by hyperarousal, intrusive reminders of the trauma, avoidance of trauma-related cues, and negative cognition and mood. This heterogeneity indicates the presence of multiple neurobiological mechanisms underlying the development and maintenance of PTSD. Fear conditioning is a robust, translational experimental paradigm that can be employed to elucidate these mechanisms by allowing for the study of fear-related dimensions of PTSD (e.g., fear extinction, fear inhibition, and generalization of fear) across multiple units of analysis. Fear conditioning experiments have identified varying trajectories of the dimensions described, highlighting exciting new avenues of targeted, focused study. Additionally, fear conditioning studies provide a translational platform to develop novel interventions. The current review highlights the versatility of fear conditioning paradigms, the implications for pharmacological and non-pharmacological treatments, the robustness of these paradigms to span an array of neuroscientific measures (e.g., genetic studies), and finally the need to understand the boundary conditions under which these paradigms are effective. Further understanding these paradigms will ultimately allow for optimization of fear conditioning paradigms, a necessary step towards the advancement of PTSD treatment methods.